Involvement of HMGB1-mediated ferroptosis in systemic diseases - Lv, Lijie; Wang, Yue; Lv, Xuan; Miao, Qiuli (Frontiers in Cell and Developmental Biology, 2025)
Ferroptosis is a distinct, iron-dependent form of regulated cell death characterized by lipid peroxidation and redox imbalance. High-mobility group box 1 (HMGB1), a nuclear protein with strong immunomodulatory capacity, has emerged as a key regulator in ferroptosis-related pathologies. Acting both as a downstream effector released during ferroptotic cell death and as an upstream amplifier of inflammation, immune activation, and metabolic dysfunction, HMGB1 plays a context-dependent dual role in disease progression. In tumor settings, HMGB1-mediated ferroptosis enhances antitumor immunity and suppresses tumor growth. Conversely, in non-neoplastic diseases, such as ischemia-reperfusion injury and inflammatory disorders, HMGB1 release exacerbates tissue damage and immune dysregulation. This review comprehensively summarizes the molecular mechanisms of HMGB1-induced ferroptosis, including its regulation via autophagy–ferritinophagy and redox signaling pathways. We further examine how the HMGB1–ferroptosis axis contributes to systemic diseases affecting the respiratory, digestive, nervous, circulatory, urinary, locomotor, endocrine, reproductive, and immune systems. Finally, we discuss emerging therapeutic strategies that target this axis with an emphasis on disease-specific interventions modulating ferroptosis, inflammation, and immune responses.